Fetal movements: Their clinical importance, and their relationship with neurodevelopment. - Arias-Obando, Ashly (2022)
The development of four-dimensional (4D) ultrasonography has made it possible to expand a type of fetal monitoring, where limbs and facial expressions are clearer to the observer in real time, increasing accuracy and the opportunity to study the fetus. Some studies have evaluated, at different stages of pregnancy, the relationship of fetal movements with neurodevelopment, finding significant differences between fetal movements in high-risk pregnancies and normal pregnancies, along with behavioral changes in fetuses with congenital disorders. Therefore, in this review article, the authors discuss the possible importance of the fetal assessment technique in the early diagnosis of diseases that involve the neurodevelopment of the fetus, observing fetal behavior that translates into movements. Fetal activity and its evaluation open a research modality in the evaluation of fetal brain function during its development.